2019
DOI: 10.1155/2019/1803624
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Evidence Linking Secondary Alexithymia to Aberrant Humor Processing

Abstract: In this review, we explore current literature and assess evidence linking secondary (acquired) alexithymia to aberrant humor processing, in terms of their neurobiological underpinnings. In addition, we suggest a possible common neuropathological substrate between secondary alexithymia and deficits in humor appreciation, by drawing on neurophysiologic and neuroradiological evidence, as well as on a recent and unique single-case study showing the cooccurrence of secondary alexithymia and deficit in humor appreci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…In addition, some research has suggested the development of primary alexithymia may be attributable to early-life trauma (see Messina et al, 2014 for a review). Secondary alexithymia may develop as a consequence of illness (Wise et al, 1990), brain injury (Patrikelis et al, 2019), or exposure to other traumatic life events (Krystal, 1968). Again, due to the cross-sectional nature of the present study, we cannot make definitive claims regarding the primary or secondary development of alexithymia in this sample.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some research has suggested the development of primary alexithymia may be attributable to early-life trauma (see Messina et al, 2014 for a review). Secondary alexithymia may develop as a consequence of illness (Wise et al, 1990), brain injury (Patrikelis et al, 2019), or exposure to other traumatic life events (Krystal, 1968). Again, due to the cross-sectional nature of the present study, we cannot make definitive claims regarding the primary or secondary development of alexithymia in this sample.…”
Section: Discussionmentioning
confidence: 99%
“…This often occurs following traumatic conditions experienced during critical periods of childhood development or due to strong emotions experienced in adulthood. In addition, secondary alexithymia has recently been related to certain diseases, such as myocardial infarction, hypertension, and rheumatoid arthritis, which suggests that it may also be a coping mechanism [73]. Moreover, acute secondary alexithymia is a temporary state-dependent condition due to distress (in the present study, the third wave of the COVID-19 pandemic in Italy), often decreasing when an acute or subacute stressful situation has finished [74].…”
Section: Discussionmentioning
confidence: 53%
“…Alexithymia is a common clinical problem among stroke survivors [ 23 , 35 , 36 , 38 , 39 , 41 ]. Its occurrence among this population of patients is associated with elevated levels of interleukin-18 [ 36 ] and damage to brain structures which lie in the right hemisphere, mainly the anterior cingulate cortex (ACC), anterior insula (AI) and prefrontal cortex (PFC) [ 23 , 26 , 27 ], though insults to left hemisphere can also play an important, yet still not fully understood role [ 41 , 42 ]. Alexithymia has a positive correlation with the severity of post-stroke PTSD [ 34 ] and is a predictive factor for depression in stroke survivors [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their work on neurobiological underpinnings of alexithymia, Meza-Concha et al [26] reviewed multiple papers concerning alexithymia and its neurobiological coordinates, mentioning damage to such structures as the amygdala, anterior cingulate cortex (ACC), anterior insula (AI), prefrontal cortex (PFC), cerebellum, and processes of abused interhemispheric connections being responsible for the occurrence of the trait. Patrikelis et al [27], who also reviewed multiple papers regarding alexithymia's neurobiological coordinates, conclude that insulting the anterior cortical midline structures like the aforementioned ACC, AI and medial prefrontal cortex (mPFC) can possibly play key roles in secondary alexithymia, as these structures take part in regulating various processes of our emotional life. Through regulating the interoceptive processing (receiving and transforming bodily states into feelings), AI regulates the conscious self-awareness of emotions [28]; ACC regulates the process of interoceptive awareness and mediates the appearance of emotional arousal, and along with mPFC regulates the limbic structures involved in generating emotions [27].…”
Section: The "Organic Alexithymia" Concept and Its Outcomesmentioning
confidence: 99%
See 1 more Smart Citation